Back Cover: Two‐Dimensional Tetrathiafulvalene Covalent Organic Frameworks: Towards Latticed Conductive Organic Salts (Chem. Eur. J. 45/2014). Issue 45 (3rd November 2014) - Jin, Shangbin; Sakurai, Tsuneaki; Kowalczyk, Tim; Dalapati, Sasanka; Xu, Fei; Wei, Hao; Chen, Xiong; Gao, Jia; Seki, Shu; Irle, Stephan; Jiang, Donglin
<x xml:space="preserve">Abstract</x> Ordered tetrathiafulvalene structures are constructed by integrating into the lattice of 2D covalent organic frameworks. The tetrathiafulvalene columnar π‐arrays offer pathways for high‐rate hole transport, determine the frontier orbit levels, and upon oxidation form organic salts that exhibit drastically improved electric conductivity by several orders of magnitude. For more details, see the Communication by D. Jiang et al. on page 14608 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>